PLANKTON STATUS OF CHAURS IN BEGUSARAI DISTRICT, BIHAR - CHOUDHARY, SWAPNA; KUMAR, UTTAM; KUMAR, UTPAL (Journal of the Inland Fisheries Society of India, 2021)
The state of Bihar, especially North Bihar, is endowed with copious aquatic wealth in the form of chaurs, swamps, ponds and rivers, which bear rich potential for inland fish production The district Begusarai, an important district in the state of Bihar lies on the Northern banks of river Ganga, geographically lying between latitude 25° 14´ N & 25° 46´ N and longitude 85° 45´ E & 86° 45´ E. The total wetland area in the district is 20,365 ha including 116 small wetlands having area less than 2.25 ha, which comprises the highest extent of wetland 10.78% of the geographical area of the district